Conceptualising context in institutional reforms of land and natural resource management: the case of Vietnam - Clement, Floriane; Amezaga, Jaime M. (2013)
Research and policy debates over natural resource management in developing countries have largely focused on identifying the set of institutions that best supports resource sustainability and poverty alleviation. We argue that beyond finding the right institutional fit for a social-ecological system, it is equally important to understand how context affects the design and outcomes of institutional reforms. We propose a refined conceptualisation of context, based on a revision of the Institutional Analysis and Development framework. We defend a systematic analysis of context, distinguishing between contextual factors affecting the fitness to local socio-ecological conditions and contextual factors that mobilise power such as political-economic interests and prevailing discourses. We illustrate our argument with empirical research on land-tenure reforms that have been implemented since the 1980s in northern Vietnam. The proposed analytical framework and conceptualisation of context allows a more pervasive understanding of contextual factors, enabling the incorporation of the forms of power that give meaning and legitimacy to institutional change.